The data collection process BPKB APPLICATIONS IN FINANCE PT.PARAMULTI USING VISUAL BASIC 6.0 - Mayasari Diyah; Irfan Irfan (Jurnal Sistem Informasi, 2009)
ABSTRACT:At current developments in computer technology is increasing, technology is able to provide the information as accurate and which are no doubt accurate lagi.Misalnya on PT.Paramulti Finance in handling the data collection process which is still manually BPKB in providing consumer finance will spend a long time penyelesaianya , especially concerning the problem statement.This program includes the application of credit payment information each time transaction, so it can be more easily and to optimize control of every month. With the help of supporting applications created with Microsoft Visual Basic 6.0 is expected to ease in knowing the credit payment information.Bibliography: 5 (1999-2006)